2008
DOI: 10.1111/j.1742-1241.2006.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Rebound platelet activation after termination of prasugrel and aspirin therapy due to confirmed non-compliance in patient enrolled in the JUMBO Trial

Abstract: Therapy with aspirin and/or adenosine diphosphate (ADP) receptor blockers is associated with better outcomes via inhibition of platelet activity, and subsequent reduction of ischemic vascular events. Non-compliance (NC) is a well-recognised hazard limiting the clinical utility of antiplatelet agents, and, probably worsening outcomes. However, comprehensive platelet characteristics of a confirmed NC patient after acute vascular event have never been reported within a major randomised trial with ADP-receptor ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
1
21
2
1
Order By: Relevance
“…These pharmacogenetic findings were in contrast to observations with clopidogrel, which might partly explain different pharmacological and clinical responses to these medications [23]. Many studies showed that CYP genetic variants had a significant influence on the pharmacokinetic and pharmacodynamic responses to clopidogrel, causing diminished antiplatelet response [24]. However, prasugrel is believed to be less affected by genotypic variability [25][26][27].…”
Section: Discussioncontrasting
confidence: 46%
“…These pharmacogenetic findings were in contrast to observations with clopidogrel, which might partly explain different pharmacological and clinical responses to these medications [23]. Many studies showed that CYP genetic variants had a significant influence on the pharmacokinetic and pharmacodynamic responses to clopidogrel, causing diminished antiplatelet response [24]. However, prasugrel is believed to be less affected by genotypic variability [25][26][27].…”
Section: Discussioncontrasting
confidence: 46%
“…[1][2][3] Among patients taking clopidogrel and aspirin for 1 year after drug-eluting stent placement, there were significant increases in proinflammatory and prothrombotic markers after clopidogrel cessation. 1 This may be due to increased production of reticulated platelets, which have a higher thrombotic potential.…”
mentioning
confidence: 99%
“…73 This patient was reported to have had at least a twofold increase in all platelet measures, with platelet activation biomarkers being higher than those observed at presentation of acute vascular event, suggesting a rebound effect in this patient. [97][98][99] ).…”
Section: Case Reportsmentioning
confidence: 71%
“…When the criteria were broadened to include patients with PCI, stroke, PAD and STEMI, most of the retrieved data were for patients who had undergone PCI. Of these: five RCTs, 50-54 two observational cohorts, 38,55 nine case series, 56-64 and 33 case reports across 17 publications [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] investigated clopidogrel and ticlopidine therapy. Only two case series 82,83 and two case reports in a single publication 84 were identified for patients who had not undergone PCI.…”
Section: Quantity Of Research Availablementioning
confidence: 99%
See 1 more Smart Citation